How to be a detective - "Mitchelhill, Barbara" (London; Andersen Press, 2017)
When one of his detectives-in-training spots a woman with nearly all of the signs of a criminal, young Damian Drooth tails her through a dog show and learns that she really is up to no good
Donated from "Book Planet", 18-4-25.
Keywords: Detective and mystery fiction-English